CHANGE MANAGEMENT IN THE RESTRUCTURING OF LPTIK INTO THE ICT SERVICE UNIT (UPA TIK) AT THE UNIVERSITY OF JAMBI (STRATEGIES, CHALLENGES, AND OPPORTUNITIES) - Rusman; Adriani, Zulfina; Fazri, Andang (Journal of Business Studies and Management Review, 2025)
Organizational restructuring serves as one of the key strategies to enhance the effectiveness of higher education governance, particularly in responding to the demands of digital transformation and national policies. This research aims to analyze change management in the restructuring of the Information and Communication Technology Development Agency (LPTIK) into the Technical Implementation Unit for Information and Communication Technology (UPA TIK) at Jambi University. The study focuses on the characteristics of the change, the change management strategies implemented, the challenges encountered, and the strategic opportunities arising from the restructuring. This research employs a qualitative approach using a case study method. Data collection was conducted through in-depth interviews with university leaders, UPA TIK leadership and staff, as well as information technology service users, complemented by document analysis. Data analysis was performed thematically, linking empirical findings to change management theories, including Lewin's model, Kotter's model, ADKAR, and McKinsey 7S. The findings indicate that the restructuring of LPTIK into UPA TIK constitutes a policy-driven and incremental organizational change, emphasizing structural adjustments and coordination pathways rather than comprehensive transformations in work processes and organizational culture. The implemented change management strategies were predominantly administrative and stability-oriented, successfully maintaining the continuity of information technology services in the short term. However, comprehensive implementation of change leadership, human resource management, persuasive communication, and change reinforcement systems remains lacking. This condition has led to symbolic resistance among staff and poses risks to the sustainability of the change in the long term. This study produces a conceptual model of change management, demonstrating that the success of organizational restructuring in higher education institutions is not solely determined by structural changes but is heavily dependent on the quality of change management strategies as a mediating variable. These findings contribute conceptually to the study of change management in higher education and provide practical implications for managing organizational restructuring in state universities.